Integration of Automotive Glazing Condition Monitoring into Fleet Management Systems - Svynchak, Andrii (Global Prosperity, 2026)
The research focuses on the conceptual architecture of integrating automotive glazing condition monitoring systems into comprehensive fleet safety management platforms within the U.S. commercial transportation sector. It examines the windshield as a high-technology sensor platform whose optical and structural integrity is a mandatory prerequisite for the effective functioning of Advanced Driver Assistance Systems (ADAS). The study redefines glazing from a passive component to a critical node within the digital telematics ecosystem, analyzing the operational and managerial mechanisms required to bridge the institutional gap in contemporary fleet management systems. As a conceptual and review-based study, the research employs a multi-tier analytical framework combining a systematic literature review (Scopus, Web of Science, Google Scholar) with a technical analysis of federal regulatory standards (FMVSS 205, 216a; 49 CFR). The methodology includes a statistical review of FMCSA crash datasets (164,347 incidents in 2023) and structured interviews with fleet operators to identify decision-making patterns. All quantitative projections are presented as indicative estimates, acknowledging the significant variability inherent in diverse fleet scales and regional environmental stressors. The primary objective is to develop and verify a four-tier conceptual model for embedding glazing integrity surveillance into existing fleet management systems. The study aims to substantiate the transition from stochastic, reactive maintenance to an IT-integrated predictive paradigm, providing a scientifically grounded roadmap for fleet operators to mitigate operational risks and enhance regulatory compliance. The findings confirm that the proposed integration is architecturally compatible with existing telematics via open API mechanisms. The study substantiates that implementing digital monitoring protocols can reduce vehicle downtime by up to 60-70% under optimal conditions. The transition to an integrated approach ensures synergy across technological, financial, and regulatory dimensions, transforming glazing control into a predictable variable of fleet safety. The research acknowledges certain limitations due to its conceptual nature, emphasizing that actual ROI may vary based on the technological maturity of the specific fleet infrastructure.